Terapi Relaksasi Otot Progresif dalam Menurunkan Tingkat Kecemasan Mahasiswa Keperawatan yang Menghadapi Ujian Praktikum: Penelitian - Rahmi Imelisa; Sinta Yusnita; Fifi Siti Fauziah Yani; Khrisna Wisnusakti; Achmad Setya Roswendi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Nursing students are someone who is taking education to become a professional nurse. In practicum exams, students are prone to anxiety. Progressive muscle relaxation is a therapy through attention to a muscle that does not require delusion. This study aims to determine the effect of progressive muscle relaxation therapy on anxiety levels in facing practicum exams in 1st year nursing students. This type of research is quantitative with a pre-experimental research design with a one group pretest-postest design. The sample size was 26 people using purposive sampling technique there are inclusion and exclusion criteria. Data collection using the HARS-A questionnaire. Data analysis was carried out, namely univariate percentage and bivariate marginal homogeneity test. The results of the marginal homogeneity test based on the results of univariate analysis showed that before being given the intervention, 34.6% of respondents experienced mild anxiety, 61.5% moderate anxiety and 3.8% severe anxiety. After being given the intervention, there was a decrease of 65.4% mild anxiety, 3.8% moderate anxiety and 30.8% did not experience anxiety. Based on the results of the bivariate test, the p value is 0.001 <0.05. There is an effect of progressive muscle relaxation therapy on anxiety levels in facing practicum exams in 1st year nursing students.